Workplace stress : what are the symptoms? / Rosliza Md Zani ... [et al.] - Md Zani, Rosliza; Ali, Syukriah; Isahak Merican, Farah Merican (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Stress is a widespread phenomenon during all humans lifespan. As a normal person, we may feel stress out of personal or family problems, and as an employee, one person feels stress due to organizational demands. Robbins and Judge (2009) defined stress as a forceful condition in which a person is challenged with a chance, a demand, or resource related to what the person wishes for and the result seems to be very important but unpredictable. The workplace is one of the main sources of stress in our lives (Ca rr , Kelley, Keaton, and Albrecht, 2011). According to authors, workplace stress is defined as “the perceived difference between professional demands and a person’s ability to carry out those demands.” Stress typically occurs when a person is faced with a r isk that the person does not feel to have the ability to cope with. When a person is having a perception that his ability is not as high as expected by managers to perform a particular job demand, it is called as “job stress”. This type of stress can be me asured by looking at the difference between expected and actual ability. If there is so much difference, the tendency to have a high workplace stress is there (Leung, Chan, and Dongyu, 2011).